Molecular and Functional Analyses of the Primordial Costimulatory Molecule CD80/86 and Its Receptors CD28 and CD152 (CTLA-4) in a Teleost Fish - Lu, Tao-Zhen; Liu, Xun; Wu, Chang-Song; Ma, Zi-You; Wang, Yang; Zhang, Yong-An; Zhang, Xu-Jie (Frontiers in Immunology, 2022)
The moderate activation of T cells in mammals requires the costimulatory molecules, CD80 and CD86, on antigen-presenting cells to interact with their respective T cell receptors, CD28 and CD152 (CTLA-4), to promote costimulatory signals. In contrast, teleost fish (except salmonids) only possess CD80/86 as their sole primordial costimulatory molecule. However, the mechanism, which underlies the interaction between CD80/86 and its receptors CD28 and CD152 still requires elucidation. In this study, we cloned and identified the CD80/86, CD28, and CD152 genes of the grass carp (Ctenopharyngodon idella). The mRNA expression analysis showed that CD80/86, CD28, and CD152 were constitutively expressed in various tissues. Further analysis revealed that CD80/86 was highly expressed in IgM+ B cells. Conversely, CD28 and CD152 were highly expressed in CD4+ and CD8+ T cells. Subcellular localization illustrated that CD80/86, CD28, and CD152 are all located on the cell membrane. A yeast two-hybrid assay exhibited that CD80/86 can bind with both CD28 and CD152. In vivo assay showed that the expression of CD80/86 was rapidly upregulated in Aeromonas hydrophila infected fish compared to the control fish. However, the expression of CD28 and CD152 presented the inverse trend, suggesting that teleost fish may regulate T cell activation through the differential expression of CD28 and CD152. Importantly, we discovered that T cells were more likely to be activated by A. hydrophila after CD152 was blocked by anti-CD152 antibodies. This suggests that the teleost CD152 is an inhibitory receptor of T cell activation, which is similar to the mammalian CD152. Overall, this study begins to define the interaction feature between primordial CD80/86 and its receptors CD28 and CD152 in teleost fish, alongside providing a cross-species understanding of the evolution of the costimulatory signals throughout vertebrates.